(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—In modern smart grids, maintaining high power quality is essential for ensuring efficient, reliable, and stable operation of electrical systems. The proliferation of nonlinear and sensitive loads has increased issues such as voltage sag, swell, harmonics, and reactive power imbalance, which adversely affect overall power performance. This paper presents a detailed modeling and simulation study of a Unified Power Quality Conditioner (UPQC) designed to mitigate power quality problems in smart grid environments. The UPQC integrates both series and shunt active power filters within a single framework to simultaneously compensate for voltage and current-related disturbances. The system is modeled and simulated using MATLAB/Simulink to evaluate its dynamic response under various operating conditions, including load variations and fault disturbances. Simulation results demonstrate that the proposed UPQC effectively mitigates harmonics, restores voltage profiles, and maintains unity power factor, thereby improving overall system performance and reliability. The findings validate the UPQC as a robust and efficient solution for enhancing power quality in next-generation smart grids.